Fifteen - Cleary, Beverly (New York : Avon, 1996)
Jane is fifteen and dreaming of a new boy friend. When she meets Stan, he seems to be the answer to her dreams.
Booklist.
Library Journal.
New York Times.
6.5.
6.5
5-8
Keywords: Adolescence -- Fiction; Dating (Social customs) -- Fiction; Love -- Fiction; Man-woman relationships -- Fiction; Adolescence -- Fiction; Dating (Social customs) -- Fiction; Love stories; Man-woman relationship -- Fiction